PENYELESAIAN TINDAK PIDANA PENCURIAN MOTOR MELALUI PENDEKATAN KEADILAN RESTORATIF SEBAGAI PEMBAHARUAN SISTEM PEMIDANAAN DI INDONESIA - Taufiq Hidayat; Jafar Sidik (Scientia Regendi, 2022)
The tendency of a person to commit a criminal act of motorcycle theft repeatedly evidenced by the number of recidivists in the crime of motor theft shows that prison is not a good enough solution to overcome crime. Restorative justice is a settlement system created by the Attorney General's Office through Perja Number 15 of 2020 by stopping the prosecution of cases. The problems discussed in this study are 1) How is the application of the concept of restorative justice as the development of the criminal system in Indonesia? 2) How is the settlement of cases at the prosecutorial level against the crime of motor theft by the public prosecutor based on a restorative justice approach? The approach method used is normative juridical and the research specifications are descriptive analytical by analyzing the applicable laws and regulations with facts in the field. Data analysis using qualitative normative methods. The results showed that: 1) The application of the concept of restorative justice, namely prioritizing the return of all circumstances as an alternative to solving criminal cases that are retaliatory (absolute theory) Restorative justice is present as the development of the criminal system in Indonesia, namely a system that emphasizes improvements in losses caused by or related to criminal acts. 2) The settlement of cases at the district attorney's level against the crime of motor theft by the public prosecutor based on the restorative justice approach is carried out by taking into account the general requirements for the application of restorative justice to the prosecutor's environment as Perja No. 15 of 2020.